Bringing Young Citizens to Vote in Elections and Refe- rendums as One of The Forms of Developing Legal Consciousness - Sergeyevna Lavrentieva, Maria; Abdel Raheem Al Ali, Naser; Ivanovna Yastrebova, Anna (Opción, 2019)
This article is dedicated to the issues of raising the level of legal and political culture in young people and their active participation in elections. Over the last years, there has been a tendency of decline in electoral activity in our country. Young citizens also do not show proper interest in elections and referendums. Political process is a major social sphere in a country and, in order for young people to actively take part in it, it is necessary to upgrade their political culture. In accordance with the provisions of the Russian Constitution, the people are the only power holder in the country and it executes its power on its own or through national and local governmental authorities. Referendum and free election are some of the forms of direct expression of the power of the people. In this article, the authors suggest their ways of engaging young Russian citizens in elections and referendums.